In situ monitoring of atmospheric nitrous acid based on multi-pumping flow system and liquid waveguide capillary cell - Yuhan Liu; Lu, Keding; HuaBin Dong; Xin Li; Peng Cheng; Qi Zou; Yusheng Wu; Xingang Liu; Yuanhang Zhang (Journal of Environment Sciences, 2016)
In the last four decades, various techniques including spectroscopic, wet chemical and mass spectrometric methods, have been developed and applied for the detection of ambient nitrous acid (HONO). We developed a HONO detection system based on long path photometry which consists of three independent modules i.e., sampling module, fluid propulsion module and detection module. In the propulsion module, solenoid pumps are applied. With solenoid pumps the pulsed flow can be computer controlled both in terms of pump stroke volume and pulse frequency, which enables the attainment of a very stable flow rate. In the detection module, a customized Liquid Waveguide Capillary Cell (LWCC) is used. The customized LWCC pre-sets the optical fiber in-coupling with the liquid wave guide, providing the option of fast startup and easy maintenance of the absorption photometry. In summer 2014, our system was deployed in a comprehensive campaign at a rural site in the North China Plain. More than one month of high quality HONO data spanning from the limit of detection to 5 ppb were collected. Intercomparison of our system with another established system from Forschungszentrum Juelich is presented and discussed. In conclusion, our instrument achieved a detection limit of 10 pptV within 2 min and a measurement uncertainty of 7%, which is well suited for investigation of the HONO budget from urban to rural conditions in China. (C) 2016 The Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences.